2020
DOI: 10.1002/bdm.2203
|View full text |Cite
|
Sign up to set email alerts
|

Keeping them honest: Promises reduce cheating in adolescents

Abstract: People frequently engage in dishonest behavior at a cost to others, and it is therefore beneficial to study interventions promoting honest behavior. We implemented a novel intervention that gave participants a choice to promise to be truthful or not to promise. To measure cheating behavior, we developed a novel variant of the mind game—the dice‐box game—as well as a child‐friendly sender–receiver game. Across three studies with adolescents aged 10 to 14 years (N = 640) from schools in India, we found that prom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 95 publications
3
16
0
Order By: Relevance
“…Developmental research has shown that young children already understand that commitments have implications for their own behaviour. From three years of age, children will keep their promise despite being tempted to play a fun game (Kanngiesser et al, 2017) and from five years of age, children will cheat less or tell the truth more frequently after promising to be honest (Heyman et al, 2015;Kanngiesser, Sunderarajan, & Woike, 2021;Lyon & Dorado, 2008;Quas, Stolzenberg, & Lyon, 2018;Talwar, Lee, Bala, & Lindsay, 2002). Moreover, starting at age three, children expect their partners to keep their commitments and, when those partners fail to honour their obligation, young children will protest (Kachel et al, 2017;Kanngiesser et al, 2017) or try to re-engage them (Gräfenhain et al, 2009).…”
Section: Young Children's Understanding Of Justifications For Breaking a Promisementioning
confidence: 99%
“…Developmental research has shown that young children already understand that commitments have implications for their own behaviour. From three years of age, children will keep their promise despite being tempted to play a fun game (Kanngiesser et al, 2017) and from five years of age, children will cheat less or tell the truth more frequently after promising to be honest (Heyman et al, 2015;Kanngiesser, Sunderarajan, & Woike, 2021;Lyon & Dorado, 2008;Quas, Stolzenberg, & Lyon, 2018;Talwar, Lee, Bala, & Lindsay, 2002). Moreover, starting at age three, children expect their partners to keep their commitments and, when those partners fail to honour their obligation, young children will protest (Kachel et al, 2017;Kanngiesser et al, 2017) or try to re-engage them (Gräfenhain et al, 2009).…”
Section: Young Children's Understanding Of Justifications For Breaking a Promisementioning
confidence: 99%
“…It is possible that children's sensitivity to messaging about descriptive and injunctive norms can help to explain other manipulations that have been shown to impact honesty, such as eliciting promises (Evans & Lee, 2010; Heyman et al, 2015; Kanngiesser et al, 2021; Lyon & Dorado, 2008; Lyon et al, 2008; Talwar et al, 2002, 2004) and telling children moral stories (Lee et al, 2014; Talwar et al, 2016, 2017). For example, perhaps the promise manipulation is effective because a promise carries an obligation to keep one's word, which can be understood in terms of its implications for what should be done (Kanngiesser et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The survey was complemented by three incentivized economic games: the dictator game ( 62 ), a money-burning task ( 63 ), and a variant of the die-under-the-cup task ( 64 ). Participants further completed the six-item version of the ring measure of social value orientation ( 39 ) and four single-item measures tapping general risk preference ( 65 ), trust, time preference ( 38 ), and impatience ( 66 ).…”
Section: Methodsmentioning
confidence: 99%